The life and legacy of Alfred Fournier (1832–1914): where timeless and precise clinical descriptions meet artistic elegance - Ramos, Mauro Cunha; Rutherford, George William; Ruwel, Andressa Goldman (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Alfred Fournier, the first Chair Professor of Cutaneous and Syphilitic Diseases at the University of Paris, had an important role in making venereology an integral part of dermatology. His contributions remain significant over a century after his passing in 1914. Objective: To present key excerpts from Fournier’s life and work and compare his clinical descriptions with current photographic images of lesions. Methods: Descriptive review of primary and secondary sources. Iconographic comparison. Results: Born in 1832, Fournier began his medical studies at Hôpital du Midi in Paris. He published influential works on chancre and acquired and congenital syphilis. Many eponyms were named after him, in particular, the Fournier’s gangrene, tibia, and teeth. He recognized the contagiousness of secondary lesions and proposed the syphilitic origin of the tabes dorsalis and other neuropsychiatric manifestations. He was President of the first International Congress of Dermatology, and his medical activity also included work in public health, especially on alcoholism and tuberculosis. His clinical descriptions of syphilis lesions are thorough, detailed, and representative of the lesions encountered in clinical practice. Conclusion: As syphilis regains importance in high-income countries and continues to overburden low- and medium-income countries, we hope that familiarization with Fournier´s career can reinforce the interest of health professionals, especially young dermatologists, in the field of sexually transmitted infections.